Reforming the public sector: personalised activation services in the UK - Stafford, B.; Kellard, K (Policy Press, 2007)
This paper highlights the degree of flexibility and personalisation in the UK’s welfare to work programmes. The Labour Government’s New Deals as originally designed were meant to provide personalised and tailor-made services and to meet the needs of individuals. The programmes have evolved and become more personalised and promote flexible service delivery. The chapter explores the Personal Adviser model and focuses on the development of New Deal for Young People and New Deal 25 Plus. In recent years a number of factors appear to have encouraged the development of more personalised activation services in the UK.